Development of Android-based SPU Learning Media in General Chemistry Course for University Students - Mellyta Uliyandari; Emilia Candrawati (Al-Ishlah: Jurnal Pendidikan, 2022)
This study aims to develop an Android-based SPU learning media using APP Inventor in the general chemistry course 1 of the Science Education study program at Bengkulu University. The method used in this study is Research and Development (RD) with a 4D (four-D) research and development model, namely definition, formulation of learning objectives, design, carried out by designing media In learning, developing (developing) the validation of learning media content by media experts and material experts, and dissemination (dissemination) through YouTube. The results obtained include the development of Android-based SPU learning media with six main contents, namely the intro, home, CPL, and CPMK pages, materials, evaluations, and about me. The validation results by material experts, media experts, and assessments by students are all in the "appropriate" category, so this application is very good to use. Student responses after using this application are also good and are in the "agree" category. It means that students agree and are interested in the SPU application used. Student learning outcomes have increased after using SPU learning media. The gain score is 0,60 and is in the "medium" category, indicating that SPU learning media effectively improves student learning outcomes in general chemistry 1 course, especially in SPU material.